POTENSI MANGROVE WONOREJO PAMURBAYA SEBAGAI SUMBER BELAJAR GEOGRAFI UNTUK MENINGKATKAN KREATIVITAS SISWA - Hendri Prastiyono; Wiwik Sri Utami; Carmela S. Dizon (Jurnal Pendidikan Geografi Undiksha, 2023)
In the last decade, the sustainability of mangrove ecosystems has been questioned even though they have millions of potentials and benefits. The effects of the COVID-19 pandemic are producing a learning crisis. This study aims to explore the potential of the Wonorejo mangroves, east coast of Surabaya (Pamurbaya) as a source of learning geography to increase students' creativity. The existing potential is expected to have an impact on students in an educative, recreational, and creative way. Empowerment of students into the mangrove environment is carried out as a form of implementing learning in the field to create creativity. The research method used is descriptive qualitative using an ecopedagogical approach. Data was collected through focus group discussions, observations, documentation, and student worksheets (LKPD). The parameters of student creativity are seen from the student projects contained in the LKPD. The data obtained will be processed using interactive analysis techniques according to Miles and Huberman. The results of this study are that the Wonorejo, Pamurbaya mangroves have the potential as a source of learning Geography to increase student creativity through environmental projects (1) geographical aspects through the one student one tree movement (Sawahon), (2) sociological aspects through barcode education (Bardu), and (3) economic aspects through cacao mangroves (Cokro) in the Pamurbaya mangrove forest area. Empowering students in the environment is a creative practice as a form of mangrove conservation so that it remains sustainable. Learning activities in the mangrove environment support the Sustainable Development Goals program, especially in the quality education sector, life below water and life on land.